Question Number 101590 by student work last updated on 03/Jul/20

p(2x+5)=(2x^2 +3x−1)Q(x+1)  if Q(−1)=3     then p(1)=?

Commented byTinku Tara last updated on 03/Jul/20

You couldnt simple have doubt  on this question when you are working  on ∫x^x ?

Answered by prakash jain last updated on 03/Jul/20

put x=−2  p(1)=(8−6−1)Q(−1)=3

Commented bystudent work last updated on 03/Jul/20

help me to write the all practice

Answered by bemath last updated on 03/Jul/20

let x+1 = z ⇒x=z−1  P(2z+3)=(2(z−1)^2 +3(z−1)−1)Q(z)  take z=−1  then P(−2+3)=(2(−2)^2 +3(−2)−1)Q(−1)  P(1)=(8−6−1)(3)  P(1)= 1×3 = 3 ★